Creatures of Prometheus, opus 43, arranged for piano - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Austria; Vienna; Gio. Cappi)
Titelauflage of the first edition of the piano score of the ballet Die Geschöpfe des Prometheus (The Creatures of Prometheus), originally published in June, 1801, by Artaria. Includes the overture and all 16 numbers.